Jihad Merawat Orang Tua Lanjut Usia: Studi Kritik Hadis - Muhamad Fadjr Lionel Ferdinand; Dody S. Truna; Asep Saeful Mimbar (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about jihad. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about jihad in the history of Tirmidhi No. 1594. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam in the implementation of jihad. This study concludes that the hadith narrated by Tirmidhi No. 1594 is relevant to be used as a basis for carrying out jihad in the form of care for elderly parents, especially those who are sick.